2022
DOI: 10.1021/acscatal.2c03367
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Modulation of the Interaction between Fe Single Atoms and WO2.72–x for Photocatalytic N2 Reduction

Abstract: In the design of photocatalysts for ammonia synthesis, the construction of effective nitrogen (N2) adsorption and activation sites is critical. Herein, Fe single atoms were effectively fixed on the surfaces of WO2.72–x nanowires. Electronic interactions between single Fe atoms and WO2.72–x resulted in a d-band center shift toward the Fermi level and thus enhancement of N2 bonding with the catalyst surface. The studies of differential charge density and electron localization reveal that there is enhanced elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Hu et al fixed Fe single atoms (Fe-SA) on the surface of WO 2.72− x nanowires via an impregnation method. 38 The d-band center of WO 2.72− x shifted toward the Fermi level from −2.58 to −1.67 eV after Fe loading, resulting in a rise of the antibonding states above the Fermi level, which caused less filling of the antibonding states and stronger adsorption of N 2 . In addition, the studies of the charge density and electron localization indicated that the localization electron existed at Fe single atoms in Fe-SA/WO 2.72− x , which was beneficial for the charge transfer to the antibonding orbital of N 2 , thereby lowering the energy barrier activation.…”
Section: Structure Engineeringmentioning
confidence: 99%
“…Hu et al fixed Fe single atoms (Fe-SA) on the surface of WO 2.72− x nanowires via an impregnation method. 38 The d-band center of WO 2.72− x shifted toward the Fermi level from −2.58 to −1.67 eV after Fe loading, resulting in a rise of the antibonding states above the Fermi level, which caused less filling of the antibonding states and stronger adsorption of N 2 . In addition, the studies of the charge density and electron localization indicated that the localization electron existed at Fe single atoms in Fe-SA/WO 2.72− x , which was beneficial for the charge transfer to the antibonding orbital of N 2 , thereby lowering the energy barrier activation.…”
Section: Structure Engineeringmentioning
confidence: 99%
“…18,59,60 Thus, the selection of appropriate preparation methods and optimization of conditions are crucial. In this section, we will briefly introduce the principles and specifics of some common preparation methods, such as thermal treatment, 95 photoreduction, 77,96,98 impregnation, 146 wet chemical synthesis, 91,104 and others 99 (Fig. 2).…”
Section: Synthesismentioning
confidence: 99%
“…In general, metals ( e.g. , Fe, 95,104,124 Mo, 91,115 Co, 147 Ru, 83,84,97,100 and Au 110,127 ) often act as adsorption and activity centers in PNRR systems. However, more studies have shown that supports can not only act as active sites ( e.g.…”
Section: Support Classificationmentioning
confidence: 99%
“…As one of the most abundant substances on earth, metal oxides/sulfides have been widely studied and applied in the fields of energy conversion and environmental protection. [ 60 ] Specifically, metal oxides/sulfides such as TiO 2 , [ 61 ] CoO, [ 62,63 ] WO 3 , [ 64 ] ZrO 2 , [ 65 ] CdS, [ 66 ] MoS 2 , [ 67 ] and ZnIn 2 S 4 [ 24 ] have O and S coordination atoms in their crystal lattice and surface that can serve as anchoring sites to stabilize single metal atoms.…”
Section: Design Preparation and Characterization Of Single‐atom Photo...mentioning
confidence: 99%
“…[ 72 ] Hu et al anchored Fe SAs on the surface of WO 2.72‐ x nanowires for N 2 reduction. [ 64 ] The loading of Fe SAs changed the electronic structure of WO 2.72‐ x and increased the catalyst's adsorption capacity for N 2 . Therefore, Fe‐SA‐4/WO 2.72‐ x showed good catalytic activity, and the formation rate of NH4+ ${\rm{NH}}_4^ + \;$ reached 186.5 µmol g −1 h −1 .…”
Section: Design Preparation and Characterization Of Single‐atom Photo...mentioning
confidence: 99%